Effects of Ramadan intermittent fasting on middle-distance running performance in well-trained runners - Brisswalter, J.; Bouhlel, E.; Falola, J. M.; Abbiss, C. R.; Vallier, J. M.; Hauswirth, C. (Clinical Journal of Sport Medicine, 2011)
Objective: To assess whether Ramadan intermittent fasting (RIF) affects 5000-m running performance and physiological parameters classically associated with middle-distance performance.